Capital budgeting - Luchtman, Kelly (Olathe : RMI Media Productions [production company] ; East Sussex : Audio Visual Sources Multimedia [distributor], 2000)
Features the capital budgeting process of Navistar. Discusses how the company uses the new capital budgeting system which looks at capital decision in context of overall business decision and incorporates projecting revenue, cost and resource element. This new system is an improvement over the way the company had carry out the traditional model.
VHS format
Keywords: Capital budget; Capital investments; Budget in business; Corporations -- Finance